Sanitary and phytosanitary standards as bridge to cross - Munasib, Abdul; Roy, Devesh (International Food Policy Research Institute, 2011)
This research assesses the effects of sanitary and phytosanitary (SPS) standards in international trade by introducing a new concept, bridge to cross (BTC), with product standards. The BTC in this paper is the regulatory gap between the exporting and importing countries with regard to any particular SPS measure. Assuming that each country's standard is binding in its own domestic markets, the standard of the importing country emerges as an effective trade barrier only when it exceeds the standard in the domestic market of the exporting country. Given the need to account for unobserved heterogeneity (multilateral resistance) in empirical trade models, if SPS regulations do not vary significantly over time, the effect of the regulation cannot be identified. However, the effect of BTC can still be identified because it varies by the pair of countries involved in the trade. As an application we apply the method to an SPS regulation relating to aflatoxin contamination in maize. In our empirical analysis we find that the effect of BTC varies by the size of the exporter and that the effect is stronger for poorer countries.